2018
DOI: 10.1159/000492554
|View full text |Cite
|
Sign up to set email alerts
|

Psoralen and Bakuchiol Ameliorate M-CSF Plus RANKL-Induced Osteoclast Differentiation and Bone Resorption Via Inhibition of AKT and AP-1 Pathways in Vitro

Abstract: Background/Aims: Psoralen and bakuchiol are the main active compounds found in the traditional Chinese medicine Psoralea corylifolia L., and have been used to treat osteoporosis. This study aims to investigate the anti-osteoporosis effects of these two compounds using osteoclasts precursor differentiation and bone absorption assays in vitro. Methods: Primary mouse osteoclasts precursor cells were induced by M-CSF (macrophage colony stimulating factor) plus RANKL (receptor activator of nuclear factor kappa-B li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 33 publications
(45 reference statements)
0
31
0
Order By: Relevance
“…Consistently, several naturally occurring coumarin compounds showed antiosteoclastic bone resorption effects in vitro and in vivo. ese include aesculin, psoralidin, daphnetin, bakuchiol, and esculetin [16,19,30,31]. us, coumarin derivatives can be used as promising natural pharmaceutical agents for the treatment of osteoporosis.…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, several naturally occurring coumarin compounds showed antiosteoclastic bone resorption effects in vitro and in vivo. ese include aesculin, psoralidin, daphnetin, bakuchiol, and esculetin [16,19,30,31]. us, coumarin derivatives can be used as promising natural pharmaceutical agents for the treatment of osteoporosis.…”
Section: Discussionmentioning
confidence: 99%
“…The osteogenic effects of BA and BK appear to be produced by up-regulation of the Wnt signalling pathway, and produce increased ALP levels, Ca serum concentration, and BMD (Lim et al, 2009; Weng et al, 2015). Further in vitro findings suggest that BK inhibits RANKL-induced osteoclast differentiation and bone resorption by disrupting the AKT and AP-1 signalling pathways (Chai et al, 2018).…”
Section: Natural Chinese Medicinesmentioning
confidence: 99%
“…Furthermore, the OVX -induced gene expression profile was reversed by PSO treatment, appearing to be mediated via the Notch signalling pathway, and resulted in regulation of the differentiation of bone mesenchymal stem cell, thus indicating the osteogenic potential of PSO for the treatment of postmenopausal osteoporosis (Yang et al, 2012). In vitro findings indicate that PSO may also attenuate osteoclast differentiation and bone resorption via inhibition of the AKT and AP-1 signalling pathways (Chai et al, 2018).…”
Section: Natural Chinese Medicinesmentioning
confidence: 99%
“…However, the effect of psoralen on the phosphorylation of ASK1, JNK, and MAPK P38 in osteoblasts and osteoclasts remains controversial and requires further study (Li F. et al, 2017;Chen et al, 2017a;Chai et al, 2018;Zhang et al, 2019).…”
Section: Clinical Researchmentioning
confidence: 99%
“…Chai et al reported that psoralen was able to significantly reduce the expression of phosphorylated JNK in osteoclasts. Finally, It has been suggested that psoralen ameliorates osteoclast differentiation and bone resorption through inhibition of AP-1 and AKT pathway activation in vitro (Chai et al, 2018).…”
Section: Inhibition Of Osteoclast Differentiation and Activationmentioning
confidence: 99%